2015
DOI: 10.1155/2015/715163
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Steel Shear Walls Behavior with Sinusoidal and Trapezoidal Corrugated Plates

Abstract: Reinforcement of structures aims to control the input energy of unnatural and natural forces. In the past four decades, steel shear walls are utilized in huge constructions in some seismic countries such as Japan, United States, and Canada to lessen the risk of destructive forces. The steel shear walls are divided into two types: unstiffened and stiffened. In the former, a series of plates (sinusoidal and trapezoidal corrugated) with light thickness are used that have the postbuckling field property under over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The most common profiles used are trapezoidal and sinusoidal. In this research, trapezoidal profile is chosen to be studied as it exhibits more ductility and higher bearing capacity compared to sinusoidal profile [15].…”
Section: Corrugated Platesmentioning
confidence: 99%
“…The most common profiles used are trapezoidal and sinusoidal. In this research, trapezoidal profile is chosen to be studied as it exhibits more ductility and higher bearing capacity compared to sinusoidal profile [15].…”
Section: Corrugated Platesmentioning
confidence: 99%
“…To date, several numerical and experimental studies have investigated the behavior of Corrugated Steel Shear Walls (CSSW) with curved and trapezoidal corrugated steel plate under monotonic and cyclic loading. Based on the comparison of the numerical results [4][5][6], trapezoidal CSSWs depicted slightly higher ultimate load, energy dissipation and toughness compared to the curved CSSWs. Furthermore, the connection between thin steel plate and boundary frame is easier for the trapezoidal corrugated plate.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of Steel plate shear walls (SPSW) considerably depends on the infilled steel plate. Several kinds of research have shown that using stiffened and unstiffened steel plates can affect the load capacity, ductility, and energy dissipation capacity of the steel walls [1][2][3][4][5][6][7][8][9][10][11][12]. Using corrugated steel plates, in the shape of trapezoids, as stiffened infilled steel plates has been of interest to researchers [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%